Edudcating Union Canada - Spencer, Bruce (Canadian Journal for the Study of Adult Education, 1994)
This article provides an overview of labour education in Canada today. It discusses the range and nature of the provision, gives examples of programs and reviews the effectiveness of this major contribution to nonformal education for working people. Résumé Dans cet article nous proposons de presenter une vue d'ensemble de l'education scolaire ouvrière au Canada. Nous discuterons de l'étendue et de la nature de l'education nous fournirons des exemples de programmes, nous réexaminerons l'efficacité de l'éducation scolaire et nous montrerons enfin quel rôle celle-ci joue dans la formation non-scolaire des ouvriers.